Difficult airway management in a patient with severe mitral and tricuspid regurgitation, rapid atrial fibrillation, and moderate pulmonary hypertension: a case report - Yan Xu; Lianxiong Liang; Jie Chen; Xiaoqiang Li (BMC Anesthesiology)
Abstract Background Given the prevalence of cardiovascular disease, encountering difficult airways in this patient population is quite common. The challenge for anesthesiologists lies not only in establishing the airway but also in managing the hemodynamic instability caused by sympathetic activation during intubation. The purpose of this report is to describe the anesthetic experience of this patient with severe mitral and tricuspid regurgitation, atrial fibrillation with rapid ventricular response, and moderate pulmonary hypertension with an anticipated difficult airway. Case presentation This case report describes intubation with fibreoptic bronchoscopy after the induction of general anesthesia in a cardiac surgical patient diagnosed with severe mitral and tricuspid regurgitation, rapid atrial fibrillation, and moderate pulmonary hypertension who underwent mitral and tricuspid valve replacements. The patient had a history of difficult intubation. Therefore, having considered that the benefits of intubation after general anesthesia induction outweighed the risks of awake intubation, the choice of fibreoptic bronchoscopy-guided intubation was performed following general anesthesia induction. No adverse events occurred throughout the proceeding. Conclusion This case highlights the importance of considering both airway safety and maintaining hemodynamic stability when cardiac surgery patients encounter an anticipated difficult airway. Awake intubation is not the only option, and intubation after general anesthesia may be considered when the benefits are evaluated to outweigh the risks.